Teknik Kuleshov Effect dalam Editing Film Fiksi Pendek Wahyu (Revelation) - Ramadhani, Adnan; Haryanto, Dwi; Suharijadi, Didik (ROLLING, 2024)
The term "mairil" generally describes an act of affection between fellow students. However, sometimes it also refers to junior students who have white, attractive, adorable physical characteristics, a face that looks like a baby face. Senior students often choose them as mairil partners. Meanwhile, the term "nyempet" is used to describe the sexual act of intercourse between male students. Generally, this is done by senior students towards their maiden partners. Mairil and nchempet behavior in the Islamic boarding school environment is the basic issue that the author will describe in this audio visual work. This film is constructed as a film with a suspense drama genre Wahyu's behavior is the basis for the creator to use the Kuleshov effect technique with the concept of visual storytelling. Another reason why this technique is applied is to present the point of view of the character Cholis who also plays an important role in the continuity of the story The artistic work process in making the film Wahyu (Revelation) begins with observation, development or developing story ideas, pre-production stages, production stages and post-production stages. The Kuleshov effect technique in image editing focuses on the audience's perception of a character's reaction to something they see, and this technique can be applied by juxtaposing a character's expression shot with a POV shot. The creator as editor was able to apply this technique in the film Wahyu (Revelation) in scene 5, and scene 15to build the audience's perception of a character's reaction to an event